Lessons on causality assessment and communications from the 2019 South-East Asia Regional (SEAR) workshop on inter-country expert review of selected Adverse Events Following Immunization (AEFI) cases. Issue 32 (6th July 2020) - MacDonald, Noni E.; Guichard, Stephane; Arora, Narendra; Menning, Lisa; Wilhelm, Elisabeth; ,
Abstract: Background: Surveillance of AEFI is fundamental for improving safety and maintaining public support for vaccination. In SEAR, billions of doses of vaccine are given annually. The objective of the 2019 SEAR AEFI training workshop was to further strengthen in-country vaccine safety, assess capacity compared to 2014 and to better integrate communication into the AEFI causality assessment program. Methods: A 3 ½ day workshop with AEFI experts from all 11 SEAR countries. Participants outlined each county's AEFI data, critiqued their AEFI program, reviewed and critiqued causality assessment of 23 anonymized serious AEFI cases and proposed communication plans for each. Results: Between 2016 and 2018, over 2.9 billion doses of vaccine were given in SEAR. Compared to 2014, AEFI detection and causality assessment skills had improved. AEFI experts' communication planning skills markedly improved during the workshop. Good concordance was found between country causality assessment findings and the workshop critiques. A list of targeted recommendations (country, regional and global levels) arose from the workshop. Conclusions: SEAR countries have much improved their AEFI detection and causality assessment expertise since 2014. Given the high volume of doses administered and the AEFI technical expertise, SEAR countries can well monitor safety of regionally produced vaccines. Integration of AEFI communication into AEFI causality assessment can help mitigate potential negative impacts of serious AEFIs.